A Gray code for cross-bifix-free sets. (11th May 2015) - BERNINI, ANTONIO; BILOTTA, STEFANO; PINZANI, RENZO; VAJNOVSZKI, VINCENT
Abstract : A cross-bifix-free set of words is a set in which no prefix of any length of any word is the suffix of any other word in the set. A construction of cross-bifix-free sets has recently been proposed in Chee et al. (2013 ) within a constant factor of optimality. We propose a Gray code for these cross-bifix-free sets and a CAT algorithm generating it. Our Gray code list is trace partitioned, that is, words with zero in the same positions are consecutive in the list.